Gamification: Evaluation of the module learns to read from the Montessori Preschool app - Marcillo, Fabricio (2025)
The integration of technology into preschool education is a relevant topic in the modern era. This study investigates technological interfaces in this area, with a focus on adapting them to the individual needs of students. Furthermore, it explores how gamification tools can improve motivation and reading and writing skills in young children. The study adopted a quantitative-qualitative approach, comparing data from children in Santo Domingo de los Tsáchilas and Pichincha. The impact of the Montessori application in teaching reading was analyzed, with varied results between provinces. Although an overall improvement in skills was observed, there were significant differences between students and the academic performance evidenced. The need to adapt educational strategies to the individual needs of each student to ensure equitable development is emphasized. A distinction is made between gamification and gamification, highlighting the potential of the latter to motivate and develop skills. Furthermore, its integration into future educational programs is suggested as an effective tool to enrich the learning process.